PEMBELAJARAN BAHASA RUSIA BAGI PEMANDU WISATA DI PULAU BALI - ANGGRAENI PURNAMA DEWI; HILMAN FAUZIA KHOERUMAN (Journal of Linguistic Phenomena (JLP), 2022)
The use of the Russian language in Bali is very important due to the large number of Russian tourists visiting the island of Bali. Even though Russian grammar is very diverse and has significant differences from Indonesian grammar, this does not reduce the enthusiasm of the students to continue learning Russian. The method used in this research is a qualitative method with a cultural approach. The results of the study show that there are more and more Russian-speaking tour guides in Bali in line with the number of Russian tourist visits which continue to show an increase from 2002-2017. Some of them learn Russian through teaching institutions, and some are self-taught. In fact, a lot of information related to tourism to the island of Bali has now been made in Russian to make it easier for Russian tourists to understand.